Prescrição médica eletrônica com verificação descentralizada utilizando Blockchain - Furtado, Thiago Ribeiro Baizi Dias (2023)
This work conducts a comprehensive analysis of medical prescriptions, examining their historical evolution and current usage. The potential integration of new technologies, such as Blockchain and Smart Contracts, to enhance these systems is explored. The research culminates in the development of a complete system, comprising a web interface and connectivity with a decentralized Blockchain network for the insertion of electronic medical prescriptions. The study delves into a dedicated examination of Blockchain technology and its frameworks, a structure that provides support for code construction, aiming for a broader and deeper understanding of the effectiveness of these technologies in the specific context of medical pres- criptions. The conclusion addresses the final version of the system, critically highlighting its advantages and disadvantages. The study provides insight into technological transformations in the context of medical prescriptions, emphasizing the opportunities and challenges associated with implementing innovative solutions in this field.